Understanding the Climate Behavior Through Data Interpretation: Java-Bali-Nusa Tenggara Case - Amartya Natayu; Fatima Tasya Kamila; Ida Bagus Gede Genta Dananjaya; Rhainna Rheizkhira Reflin; Muhamad Rausyan Fikri (Faculty of Engineering and Technology, Sampoerna University, 2021)
As an archipelago country in the equator, Indonesia has a tropical climate and often is subjected to monsoonal circulation. The geographical location affects Indonesia to have two seasons, which are the rainy season and drier season. Every season has its characteristic impacts against the mean temperature and rainfall rate. This research aims to analyze Indonesia’s mean temperature and rainfall rate data concerning its tropical climate. The areas observed are limited to Java, Bali, and Nusa Tenggara Island from January 2019 to December 2020. The data gathered from the official Badan Meteorologi Klimatologi dan Geofisika (BMKG) website were processed using MATLAB, and Spearman’s correlation was applied to analyze the rainfall and temperature data. From the observation, this study discovered that the mean temperature data is stable throughout the areas but reaches maximum during the transition between rainy and drier seasons and minimum during the middle of the rainy season. The data observation is often fluctuated, even though showing less rain during the drier season and more during rainy seasons. The fluctuation is affected by the geographical fact that Indonesia has a large water surface, which makes evaporation easily induced by warm tropical temperatures.